Thermal Stability and Reproducibility Enhancement of Organic Solar Cells by Tris(hydroxyquinoline)gallium Dopant Forming a Dual Acceptor Active Layer - Muhammad, Fahmi F.; Sulaiman, Khaulah (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Nowadays, the main barriers facing organic solar cells (OSCs) from being commercialized and widely applied are their weak thermal stability and reproducibility problems. To tackle these problems, researchers usually consider various strategies which include modification in the devices architectural design, utilizing low energy gap materials, functionalizing their active layers, and the use of various optimization procedures. In this research work, we are specifically focused on the utilization of a small molecular organometallic, tris(hydroxyquinoline)gallium (Gaq3), as a secondary acceptor dopant, aiming at improving thermal stability, and reproducibility of OSCs. All-solution processed technique with the help of spin coater was used to deposit the active layer of the devices. Results showed that the addition of 29% molar fraction of Gaq3 into the devices active layer has considerably improved the thermal stability, photo-absorption, and reproducibly of the solar cells thanks to the excellent thermal stability and electron mobility of Gaq3 molecules. Our devices based on DH6T: PCBM:Gaq3 performed highest stable performance at 180°C, implying higher thermal stability compared to that of the reported P3HT: PCBM:F8BT and PTB7:PCBM: F8BT based solar cells. In spite of improved reproducibility, the efficiency of the devices was increased by 5.8 times compared to that of the control ones.